Pelindungan Hukum Terhadap Personal Guarantee yang Melepaskan Hak Istimewa dalam Perkara Kepailitan (Studi Putusan Pengadilan Niaga Nomor 24/Pdt.Sus- Gugatan Lain Lain/2021/PN.Niaga.Jkt.Pst.) - Maristella Pratiwi Damanik; Sunarmi Sunarmi; Mahmul Siregar; Dedi Harianto (Dinasti Review Publisher, 2024)
A personal guarantor has special rights granted by law to protect themselves while fulfilling their obligations. However, in practice, these special rights are often waived, which has significant legal implications, especially in the context of debtor bankruptcy. This research aims to understand the position of a personal guarantor in situations where the debtor is bankrupt, analyze the legal protection for guarantors who waive their special rights in bankruptcy cases, and elaborate on the legal considerations of the Judicial Panel regarding guarantor protection in decision No. 24/Pdt.Sus-Gugatan Lain Lain/2021/PN. Niaga.Jkt.Pst. The method used is normative juridical with a descriptive nature, using a statutory and case approach. Data is obtained from secondary sources, including primary, secondary, and tertiary legal materials, through literature studies and field studies. The analysis is conducted qualitatively with deductive conclusion drawing. The results of the study show that personal guarantors are also considered debtors in the event of debtor bankruptcy, benefiting creditors in fulfilling their claims. Preventive legal protection is provided through comprehensive information, maximum guarantee limits, bankruptcy provisions, and the right of subrogation. Repressive legal protection is carried out through the filing of other lawsuits in commercial courts, as seen in Decision No. 24/Pdt.Sus-Gugatan Lain Lain/2021/PN.Niaga.Jkt.Pst. which granted the lawsuit of the personal guarantor.